1984
DOI: 10.1002/aja.1001710309
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reorganization during resumption of arrested meiosis in the mouse oocyte

Abstract: Correlated nuclear and cytoplasmic reorganizations during the 14 hr of reactivated meiosis in vivo and in vitro were examined in the laboratory mouse. Observations of living oocytes by differential interference contrast microscopy, and by fluorescent microscopy with nontoxic mitochondrial and DNA-specific probes, enabled us to determine that the major cytoplasmic reorganization involved two mitochondrial translocations associated with two stages of nuclear maturation. These observations were confirmed at the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
149
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(176 citation statements)
references
References 32 publications
20
149
2
Order By: Relevance
“…A major biological function of triacylglycerols is to serve as a storage form of metabolic energy in preparation for specific developmental events such as the hatching of the blastocyst (10). In embryos of different species, mitochondria have been colocalized with lipid droplets but the functional significance of these associations is unclear (8,29,39). They are thought to provide a reserve of lipid for oxidation by mitochondrial oxidases.…”
Section: Discussionmentioning
confidence: 99%
“…A major biological function of triacylglycerols is to serve as a storage form of metabolic energy in preparation for specific developmental events such as the hatching of the blastocyst (10). In embryos of different species, mitochondria have been colocalized with lipid droplets but the functional significance of these associations is unclear (8,29,39). They are thought to provide a reserve of lipid for oxidation by mitochondrial oxidases.…”
Section: Discussionmentioning
confidence: 99%
“…Transient and focal upregulation of mitochondrial respiration may be an important mechanism by which differential intracytoplasmic energy demands in the maturing oocyte and early embryo are met without involving the entire mitochondrial complement (Van Blerkom & Runner 1984). Indeed, Dumollard et al (2004) demonstrated that ATP supply and demand are tightly coupled in the MII mouse oocyte and newly fertilized egg, suggesting that up-or down-regulated mitochondrial activity is likely stage-specific and differentially localized within the cytoplasm during early development.…”
Section: Mitochondria As Metabolic Forces In Early Developmentmentioning
confidence: 99%
“…During maturation of the mouse oocyte in vitro, mitochondria translocate to the perinuclear region along microtubular arrays extending from perinuclear microtubular organizing centers (Van Blerkom 1991) to form a sphere of organelles that encloses the condensing bivalent chromosomes and, later, the nascent metaphase I and II spindles (Van Blerkom & Runner 1984, Tokura et al 1993. After fertilization in the mouse (Van Blerkom & Runner 1984), hamster (Bavister & Squirrell 2000) and human (Van Blerkom et al 2000), mitochondria migrate to the perinuclear region, again by a microtubulemediated process, to form a condensed aggregate surrounding the opposed pronuclei. A similar transient perinuclear accumulation occurs in each blastomere during the early cleavage stages.…”
Section: Spatial Remodeling Of Mitochondria Is a Common Aspect Of Earmentioning
confidence: 99%
“…The distribution of mitochondria changes during oocyte maturation and fertilisation with the aim of bringing mitochondria to the region of the cell where a higher level of ATP (Van Blerkom & Runner 1984) or calcium (Sousa et al 1997) is required. It has been demonstrated that mitochondrial function and the cytoplasmic ATP level can affect fertilisation, resulting in a significant increase in blastocyst rates or their total failure after IVF (Van Blerkom et al 1995, Liu et al 2000.…”
Section: Introductionmentioning
confidence: 99%